Pengaruh Oksigen Terlarut (Do) Dalam Budidaya Perairan - Telaumbanua, Merlis (Jurnal Perikanan dan Kelautan, 2025)
Dissolved oxygen (DO) serves as a crucial parameter in assessing water quality and the health of aquatic ecosystems. The availability of oxygen is essential for the respiratory process of many organisms, such as fish and shrimp. This research explores the elements that influence DO levels, its impact on aquatic life and management methods based on a literature review over the past five years. Several factors such as temperature, photosynthesis, respiration, organic pollution and water movement can significantly affect DO levels. Low DO levels (below 3 mg/L) can cause stress and even death to organisms, especially in contaminated areas. In aquaculture practices, daily changes in DO levels create problems. DO management can be done through the use of aeration technology, utilization of riparian vegetation, and monitoring using IoT-based sensors. Adaptive and collaborative approaches are key factors in maintaining the sustainability of aquatic ecosystems amidst the challenges of climate change and human activities.